The journal of civic information - LoMonte, Frank D.; Cuillier, David; University of Florida. College of Journalism and Communications. Brechner Center for Freedom of Information; LibraryPress@UF (Frank LoMonte, J.D, 2019)
An open-access, interdisciplinary journal that publishes peer-reviewed research related to the field of accessibility of public information. This journal will bring together research from across disciplines and methodologies, including law, public administration, journalism, information science, sociology, and any others concerned with the access, dissemination, use, and effects of civic information.
Keywords: Freedom of information : Periodicals; Civics : Periodicals; Press : United States : Periodicals; Civics; Freedom of information; Press; United States